Transformational Leadership Style of Kiai Hasan Abdullah Sahal at Pondok Modern Darussalam Gontor - Marlia, Ana Dwi; Azzahra, Hanifah; Lydia Jati, Alvina; Fayyazah, Arjuw; Indra Kusuma, Hanif (JSP: Jurnal Studi Pesantren, 2025)
This research presents the transformational leadership of Kyai Hasan Abdullah Sahal in managing the modern Islamic boarding school darussalam gontor, ensuring gontor remains active in educating and teaching the students. In the face of rapid global developments, gontor has managed to balance Islamic education with the advancement of the times. In carrying out his duties as a Kyai at the darussalam gontor boarding school, Kyai Hasan Abdullah Sahal applies transformational leadership in educating his students. The study of Kyai Hasan Abdullah Sahal's leadership is particularly interesting due to his transformational leadership style, inspirational motivation, and spiritual values in educating his students, shaping them into faithful and pious individuals, possessing noble character, resilient and steadfast in personality, and committed to upholding Islam and its glory. As a result, both the students and alumni of the darussalam gontor boarding school contribute positively to both national and international spheres, providing benefits from their knowledge in both ordinary society and government. This research employs a qualitative approach of library research. The findings indicate that Kyai Hasan, in leading the modern darussalam gontor boarding school, embodies values that align well with the advancement of civilization, characterized by transformational leadership, inspirational motivation, spiritual values, and exemplary inspiration. The outcome of all the values imparted by Kyai Hasan Abdullah Sahal is that the students are able to apply Islamic values in facing the challenges of the times